Permeability and selectivity study of polysulfone membrane for gas separation - Farhana, Hasbullah (2009)
Polysulfone (PSU) membrane is one of the economical and potential membranes to be used in gas separation process. Polysulfone flat sheet membrane were fabricated from 22.0 wt% polysulfone, 31.8 wt% N,N-dimethylformamide, 31.8 wt% tetrahydofuran and 14.4 wt% ethanol using dry/wet phase inversion process. Eight different samples were tested. The permeability of the membranes were tested using the gas permeation unit with pressure of 1.5-2.5 bar and were tested with CO2, CH4, N2 and also O2. Among all these eight types of membrane tested, several show that the behavior of polysulfone membrane to permeate CO2 relies on the treatment that the membranes undergo and the temperature of the coagulation bath. Thus, the most excellent value of permeability for CO2 among eight types of membranes tested was 4.98 x 10-3 cm3/cm2.s.cmHg which was PSU membrane immersed in a 4°C coagulation bath and treated with polydimethylsiloxane (PDMS) as a coating agent with the selectivity value of 1.36.From the data and result collected it is to be proved that temperature of coagulation bath and also the coating agent for membrane treatment play a major role in affecting PSU membrane permeability and selectivity as a whole.